Acute fibrinous and organizing pneumonia: A report of 13 cases in a tertiary university hospital. Issue 27 (July 2016) - Gomes, Rita; Padrão, Eva; Dabó, Hans; Soares Pires, Filipa; Mota, Patrícia; Melo, Natália; Jesus, José Miguel; Cunha, Rui; Guimarães, Susana; Souto Moura, Conceição; Morais, António
Abstract: Introduction: Acute fibrinous and organizing pneumonia (AFOP) is a rare diffuse pulmonary disease, but it is not yet known whether it is a distinct form of interstitial pneumonia or simply a reflection of a tissue sampling issue. Methods: Cross-sectional evaluation of clinical and radiological findings, treatments, and outcomes for patients with histologically confirmed AFOP at a tertiary university hospital between 2002 and 2015. Results: Thirteen patients (7 women, 53.8%) with a mean ± SD age of 53.5 ± 16.1 years were included. The main symptoms were fever (69.2%), cough (46.2%), and chest pain (30.8%). All patients presented a radiological pattern of consolidation and 5 (38.5%) had simultaneous ground-glass areas. Histology was obtained by computed tomography-guided transthoracic biopsy in 61.5% of cases and by surgical lung biopsy in the remaining cases. Several potential etiologic factors were identified. Eight patients (61.5%) had hematologic disorders and 3 had undergone an autologous hematopoietic cell transplant. Two (15.4%) had microbiologic isolates, 5 (38.4%) had drug-induced lung toxicity, and 2 (15.4%) were classified as having idiopathic AFOP. In addition to antibiotics and diuretics used to treat the underlying disease, the main treatment was corticosteroids, combined in some cases with immunosuppressants. Median survival was 78 months and 6 patients (46.2%) were still alive at the time of analysis. Conclusion: Our findings for this series of patients confirm that AFOP is a nonspecific reaction to various agents with a heterogeneous clinical presentation and clinical course that seems to be influenced mainly by the severity of the underlying disorder.